"There's not much we can do…" researcher-level barriers to the inclusion of underrepresented participants in translational research. Issue 1 (11th November 2022) - Passmore, Susan Racine; Kisicki, Abby; Gilmore-Bykovskyi, Andrea; Green-Harris, Gina; Edwards, Dorothy Farrar
Abstract: Introduction: The lack of diversity in health research participation has serious consequences for science as well as ethics. While there is growing interest in solving the problem, much of the work to date focuses on attitudes of distrust among members of underrepresented communities. However, there is also a pressing need to understand existing barriers within the cultural and structural context of researchers and research staff. Methods: This study adopted a sequential exploratory mixed-methods design to allow for a focused examination of barriers to inclusive research recruitment among researchers and staff. Barriers first identified from an initial quantitative investigation (web-based survey; n = 279) were further explored through qualitative methods (key informant interviews; n = 26). Participants were investigators and research team members in both phases of the study. Results: The survey revealed a paradoxical disconnect between participants' reported belief in the abstract value of diversity in research participation (87.1% important/extremely important) and belief in it as an important goal in their own specific research (38.3% important/extremely important). Interviews reveal that researchers and staff perceive many barriers to the recruitment of members of underrepresented groups and hold a general view of diversity in research as an impractical, even unattainable, goal. Conclusions: It is crucial that principal investigators not only understand the consequences of the continued exclusion of marginalized groups from research but also implement strategies to reverse this trend and communicate with research staff on the issue. While individual bias does play a role (ex: a priori assumptions about the willingness or ability of members of underrepresented groups to participate), these behaviors are part of a larger context of systemic racism.